The devil's bible - Berry, Steve, 1955- (Berry, Steve, 1955- Cotton Malone novels., 2026)
"Former Justice Department operative, Cotton Malone, is called to Sweden when the younger sister of King Wilhelm I is kidnapped. The ransom demand? Hand over an 800-year-old book, the Codex Gigas--the largest illuminated medieval manuscript in the world. Claimed as warloot from Bohemia in 1648, it's been kept in Stockholm for nearly 400 years. Along the way it also acquired another more mysterious moniker...The Devil's Bible. Now the Czech Republic wants the codex back, and Sweden has agreed to return it, but forces are at work to stop that deal from happening. The likely instigator? Russia. Who is also top of the list for possible kidnappers. It's up to Cotton and Cassiopeia Vitt to locate the king's sister, secure the codex, and thwart the Russians. Yet nothing is as it seems. Trusted allies become hostile enemies. Long-standing enemies suddenly shift into partners.Making matters worse, an array of conflicting personalities re-emerging from Cotton's past, transforming an already chaotic international situation into something far more personal and deadly."--Providedby publisher.